Acute peritonitis caused by the acute pancreatitis of an ectopic pancreas in a jejunal duplication, in an adult with intestinal malrotation: a case report - Chihiro Yoshikawa; Kazuhiro Migita; Ichiro Yamato; Masato Ueno; Hisanori Kashizuka; Koichi Murakami; Hirofumi Ishikawa (Surgical Case Reports)
Abstract Background Intestinal duplication and ectopic pancreas are two rare independent congenital anomalies. Few reports describe cases of patients with ectopic pancreas in an intestinal duplication causing acute peritonitis. Case presentation A 31-year-old man was admitted to the hospital for epigastric pain. The patient was diagnosed with acute peritonitis caused by the acute pancreatitis of an ectopic pancreas in a jejunal duplication, with intestinal malrotation. The patient underwent the partial resection of the jejunum and Ladd’s procedure. The histopathological findings indicated ectopic pancreatitis in the jejunal duplication. Conclusions We presented the case of acute peritonitis caused by the acute pancreatitis of an ectopic pancreas in a jejunal duplication in an adult with intestinal malrotation. Surgery is the primary treatment and is necessary for a definitive diagnosis.